THE IDENTIFICATION OF CHARACTER EDUCATION ON JESSE AARONS’ CHARACTERIZATION IN BRIDGE TO TERABITHIA BY KATHERINE PATERSON - Dewi, I Gusti Ayu Triska Sri Urmila; Juniarta, Putu Adi Krisna; Mahendrayana, Gede (Universitas Pendidikan Ganesha, 2021)
Literature has been effectively used to transfer values to children even school existed (Edgington, 2002), yet the task for selecting good literature is not simple. Therefore, this study aims to analyse a children literature entitled Bridge to Terabithia by Katherine Paterson, in order to reveal the values of character education proposed by Kemendikbud (2016) on Jesse Aarons’ characterization. This study applies the interactive model of qualitative data analysis by Miles et al. (2014). Through Jesse Aarons’ characterization, it is found out that he possessed 29 characters and 25 of them belong to the values proposed by Kemendikbud (2016). Those values are religious, peace-loving, tolerant, wise, nature-loving, nationalist, self-sacrificing, achiever, patriotic, disciplined, independent, hardworking, tough, creative, courageous, mutual-cooperative, democratic, nonviolent, solidarity, voluntary, integrity, honest, loyal, fair, and responsible.